Posteromedial opening wedge high tibial osteotomy has favourable outcomes in simultaneous medial meniscus posterior root repair and varus medial knee osteoarthritis patients without concomitant root tear - Ali Engin Dastan; Elcil Kaya Bicer; Huseyin Kaya; Mehmet Argin; Emin Taskiran (Journal of Orthopaedic Surgery and Research)
Abstract Purpose To evaluate the radiological and clinical outcomes in two patient groups: first, varus aligned medial meniscus posterior root tear (MMPRT) patients who underwent posteromedial open wedge high tibial osteotomy (PMOWHTO) and simultaneous root repair; second, patients with varus medial knee osteoarthritis without MMPRT who underwent PMOWHTO. Methods Patients had MMPRT repair concomitant with PMOWHTO and varus medial knee osteoarthritis without concomitant root tear patients who underwent PMOWHTO and were reviewed. Radiographic parameters, medial meniscus extrusion (MME) and Knee Society Scores [KSSs, including the following subscores: knee score (KS) and knee function score (KFS)] were evaluated. Continious variables are expressed as the median and interquartile range (IQR) [IQR: (Q1;Q3); Q1: median of lower half, Q3: median of upper half]. The minimum follow-up period was 24 months [29 (28;35) months]. Results A total of 36 knees of 34 patients underwent PMOWHTO were included. Patients were divided into two groups according to the presence or absence of a MMPRT. Nineteen of the 36 knees had MMPRTs, and all of them had concomitant root repair (Group 1). Seventeen of the 36 patients did not have MMPRTs (Group 2). The posterior tibial slope (PTS) decreased postoperatively in a total of 36 knees (p < 0.001). There were no significant changes in MME postoperatively in any intragroup comparison. The preoperative and follow-up MMEs of Group 1 were greater than those of Group 2 (p < 0.001). The KSs and KFSs in both Group 1 and Group 2 increased during follow-up [KS; Group 1: 43 (36;53) vs. 86 (84;95), p < 0.001. Group 2: 49 (45;57) vs. 89 (80;93), p < 0.001. KFS; Group 1: 60 (50;60) vs. 90 (80;100), p < 0.001. Group 2: 60 (50;60) vs. 80 (80;90), p < 0.001]. All knees achieved minimal clinically important difference (MCID) in terms of KSs. Eighteen (95%) knees achieved MCID in Group 1, and 17 (100%) achieved MCID in Group 2 in terms of KFSs. There were no differences between Groups 1 and 2 in terms of preoperative and follow-up KSs or preoperative KFSs. The follow-up KFSs in Group 1 was significantly greater than that in Group 2 (p = 0.032). Conclusions PMOWHTO has favourable clinical and radiological outcomes and prevents PTS increase in simultaneous MMPRT repair and varus medial knee osteoarthritis patients without concomitant root tear. Level of evidence Level IV, case series.